2020
DOI: 10.1177/1747021820973954
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of social anxiety and other individual differences on gaze-directed attentional shifts

Abstract: Gaze direction is a powerful social cue, and there is considerable evidence that we preferentially direct our attentional resources to gaze-congruent locations. While a number of individual differences have been claimed to modulate gaze-cueing effects (e.g., trait anxiety), the modulation of gaze cueing for different emotional expressions of the cue has not been investigated in social anxiety, which is characterised by a range of attentional biases for stimuli perceived to be socially threatening (e.g., Mansel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 83 publications
3
14
0
Order By: Relevance
“…These findings confirm the amygdala's role in encoding the perceived threat level of faces, as well as the more general assumption that the amygdala encodes the relevance or significance of a stimulus to the observer [94]. These results suggest that individual anxiety levels may explain inconsistent findings from previous studies [95]. Straube and colleagues [83] investigated whether the amygdala is activated by a gaze in response to threat relevance or facial expression by testing its activation during the observation of neutral, happy and angry faces with either a direct or averted gaze.…”
Section: Conjoint Processing Of Emotional Expressions and Gaze Direct...supporting
confidence: 83%
“…These findings confirm the amygdala's role in encoding the perceived threat level of faces, as well as the more general assumption that the amygdala encodes the relevance or significance of a stimulus to the observer [94]. These results suggest that individual anxiety levels may explain inconsistent findings from previous studies [95]. Straube and colleagues [83] investigated whether the amygdala is activated by a gaze in response to threat relevance or facial expression by testing its activation during the observation of neutral, happy and angry faces with either a direct or averted gaze.…”
Section: Conjoint Processing Of Emotional Expressions and Gaze Direct...supporting
confidence: 83%
“…This finding also suggests that gaze cues trigger reflexive attention orienting. A recent study in a sample of 100 women reported that emotional facial expressions (i.e., angry and fearful faces) did not modulate gaze-triggered attention orienting ( Talipski et al, 2020 ). However, many studies have demonstrated that dynamic presentations of fearful ( Tipples, 2006 ; Uono et al, 2009a ; Lassalle and Itier, 2013 , 2015b ; Neath et al, 2013 ; McCrackin and Itier, 2018 ) and other emotional faces (angry: Lassalle and Itier, 2013 , 2015b ; Liu et al, 2019 ; Neath et al, 2013 ; surprised: Lassalle and Itier, 2013 , 2015b ; and happy: McCrackin and Itier, 2019 ) enhance attention orienting, compared with neutral faces.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Lassalle and Itier (2015a) , McCrackin and Itier (2019) used the dynamic cues; they found that a stronger autistic trait (i.e., attention to detail) was associated with a weaker gaze-cueing effect from fearful and happy faces. In contrast, Talipski et al (2020) used static emotional faces which appeared prior to the change of their gaze direction; they did not find any emotional enhancement of the gaze-cueing effect, nor did they find any association between autistic traits and the gaze-cueing effect of emotional faces. Thus, the evidence is not conclusive regarding the association between the gaze-cueing effect and autistic traits in the general population.…”
Section: Introductionmentioning
confidence: 85%
“…Following on from this, given gaze-cueing tasks are often used as a way to compare gaze following behavior between clinical or subclinical goups and healthy controls (e.g., see Dalmaso et al, 2013, 2015; Dawel et al, 2015; Langdon et al, 2017; Magnée et al, 2011; Marotta et al, 2018; Narison et al, 2020; Talipski et al, 2021; Uono, Sato, & Toichi, 2009; Wei et al, 2019), an important avenue for future research is to determine whether performance on gaze-cueing tasks is related to performance on well-established measures of social perception and real-life social functioning. Such an assessment would be particularly valuable given that social cognitive function is now firmly established as a critical predictor of mental health and well-being, and there is a need for objective, bias free measures to be developed (Henry et al, 2016).…”
Section: Discussionmentioning
confidence: 99%